1992
DOI: 10.1063/1.107852
|View full text |Cite
|
Sign up to set email alerts
|

Transport critical currents in spray pyrolyzed films of TlBa2Ca2Cu3Oz on polycrystalline zirconia substrates

Abstract: Large critical currents with a relatively weak magnetic field dependence are obtained in thick films of TlBa2Ca2Cu3Oz. Transport measurements indicate Jc ≳105 A/cm2 at 77 K, zero field, and Jc≳104 at 60 K in a 2 T field applied along the c-axis. The observed behavior is attributed to a large degree of uniaxial alignment of platelike grains, and to superior intragranular flux pinning. These results are consistent with recent theories concerning the nature of vortices in highly anisotropic (layered) superconduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…In a first step a polycrystalline ͑Tl͒BaCaCuO precursor film, either thallium free or containing thallium, was deposited by several methods such as sputtering, 2 laser ablation, [3][4][5] or spray pyrolysis. 6 In a second step thallium was introduced into the precursor film by a heat treatment in the presence of O 2 and Tl 2 O vapor for forming of the Tl-1223 phase. It has been found that a platelike structure developed during the heat treatment, with grain boundaries, and weak links that are responsible for low values of the critical current density.…”
Section: ͓S0003-6951͑96͒02807-2͔mentioning
confidence: 99%
“…In a first step a polycrystalline ͑Tl͒BaCaCuO precursor film, either thallium free or containing thallium, was deposited by several methods such as sputtering, 2 laser ablation, [3][4][5] or spray pyrolysis. 6 In a second step thallium was introduced into the precursor film by a heat treatment in the presence of O 2 and Tl 2 O vapor for forming of the Tl-1223 phase. It has been found that a platelike structure developed during the heat treatment, with grain boundaries, and weak links that are responsible for low values of the critical current density.…”
Section: ͓S0003-6951͑96͒02807-2͔mentioning
confidence: 99%
“…Superconductor tapes of silver-sheathed (Tl,Pb)(Sr,Ba) 2 Ca 2 Cu 3 O y have been investigated by Ren et al [26, 27], and Salazar et al [28]. The processing of 1223 into wire and tape has been achieved by several alternative methods, including electrophoresis [29], powder in tube [28], and a two-step process including thallination of tape precursors [30]. Silver has been favored as a foundation for the wire or tape, largely because of its promotion in 1223 grain alignment, and the resulting improvement in superconducting properties.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, using the traditional two-step method, a coexistent TlBa 2 CaCu 2 O 7 (Tl-1212) or Tl 2 Ba 2 CaCu 2 O 8 (Tl-2212) phase often emerges in Tl-1223 films, which degrades the Tl-1223 film properties. [7,8] To overcome the above challenge, many strategies have been proposed to improve the purity of Tl-1223. For example, by partial substitution of Tl atoms with Bi or Pb and replacing most Ba atoms with Sr, the ratio of the Tl-1212 or Tl-2212 phase in entire Tl-1223 phase crystal can be reduced.…”
mentioning
confidence: 99%